Dampak Perbaikan Jalan Terhadap Peningkatan Ekonomi Masyarakat Di Desa Mergosari Kecamatan Tarik Kabupaten Sidoarjo: Indonesia - Dita Armah Zuria; Nur Azlinda Herawati; Putresa Eka Irmandini; Yani Septia Rachmawati; Putri Sefhiatul Rohma; Ida Faizahtun Nafiah; Marsianus Aparato; Goldensia Katarina Nay; Rheyna Putri Arditiya; Kurniatul Putri Mukhfidah; Anggraeni Retno Pangestu; Suyono Suyono (Politeknik Kampar, 2024)
This research aims to find out the impact of road improvements on improving the community's economic business in Mergosari village, Tarik, Sidoarjo. This research method uses qualitative research with descriptive methods. Data collection was done by conducting in-depth interviews with descriptive analysis method. The results showed that the impact of road improvements had a significant positive impact on increasing the economic efforts of the community in Mergosari village, Tarik, Sidoarjo. The implications of this research can be used as a basis for improving sustainable infrastructure development strategies to support local economic growth and community welfare in the region.